MAIN TOOLS OF STATE PLANNING AND FINANCIAL SUPPORT OF GEOLOGICAL STUDIES IN UKRAINE - Vyzhva, S.; Kurylo, M.; Balega, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Main principles and mechanism of financial support for geological exploration in Ukraine are defined. Dynamics and structure of the State budget expenditures for geological industry are studied in context of the state functions. The paper is based on conclusions that the level of financing for the geological industry remains stably unpredictable with stable growth of overall level of the state's financial viability (in the equivalent of the national currency). Costs for the geological industry lose their priority in the context of their financial support by state funds. Place of the State Service of Geology and Mineral Resources of Ukraine is defined as the central executive service implementing the state policy in direction of geological study and rational use of mineral resources. State financing of geological industry at the national level takes place directly through budget programs, amount of expenditures of which is determined by Laws of Ukraine "About the State Budget" for every year. Main manager of these financial resources is the Ministry of Environment of Ukraine, and the responsible executive is the State Service of Geology and Mineral Resources of Ukraine. Implementation of State Service of Geology and Mineral Resources of Ukraine' functions takes place within two budget programs – "Management of Geological Exploration and Subsoil Using " and "Development of the Mineral Raw Materials Base" which provides direct financing of the National development program of mineral base of Ukraine for period to 2010 and 2030. The peculiarities and implementation state of national programs development of mineral base of Ukraine for period to 2010 and 2030 are estimated. It was defined that the National program for period to 2010 had to be provided by 61.8% with public funds and by 38.2% with other sources. Actually, the National program was financed with public funds by 72.2% of target index, which caused partial or complete unrealization of certain tasks declared by law. The basis for financing the National development program of mineral base of Ukraine for period to 2030 was 13.8% of state financing and 86.2% of other sources' financing. The first stage (2011-2012) of the Program until 2030 was realized by 66.1%. In general, the financing of the Program until 2030 in part of state financing for 2018 was realized by 6.1%. Actually, the National development program of mineral base of Ukraine for period to 2030 is not correctly reflected at budget programs' passports, which directly show the level of its implementation and efficient use of appropriations. It makes impossible to provide qualitative assessment and appropriate recommendations concerning these issues. It should also be noted that it is impossible to analyze implementation of National development program of mineral base of Ukraine in part of their private financing, as there is no annual enterprises reporting forms of real sector of such financing.
Keywords: geological industry; mineral resource base; budget programs; financial support of exploration; planning